Normal gray matter volumes in women recovered from anorexia nervosa: a voxel-based morphometry study. Issue 1 (December 2016) - Bang, Lasse; Rø, Øyvind; Endestad, Tor
Abstract Background Anorexia nervosa (AN) has consistently been associated with reduced gray (GM) and white matter (WM) brain volumes. It is unclear whether GM alterations are present following recovery from AN, as previous findings are inconsistent. The aim of the present study was to determine if women recovered from AN exhibit reduced global or regional GM volumes. Methods Global GM and WM, as well as regional GM volumes, were investigated in 22 women recovered from AN and 22 age-matched healthy controls using magnetic resonance imaging. Women were considered recovered if they had maintained a body mass index above 18.0 and had not engaged in binge eating, purging, or restrictive eating behaviors during the past year. Results There were no significant differences between recovered AN women and healthy controls in terms of GM and WM volumes. There were also no significant differences between restricting and binging-purging AN subtypes. Lowest lifetime weight was positively correlated with regional GM volumes in the precuneus and insula. Conclusions The present study showed that regional GM and global GM and WM volumes were similar for women long-term recovered from AN and age-matched healthy controls. Further research is needed to determine the extent to which illness severity affect regional GM volumes.